Dermoid Cyst Within Concha: A Case Report - Sevil Nasirmohtaram (Acta Medica Iranica, 2016)
Dermoid cysts are congenital anomalies derived from ectoderm. They are rare in head and neck region and especially in pinna. We presented an 8-year-old girl with a dermoid cyst in the conchal region of auricle which was treated with complete surgical resection.